Taking Decisions Too Seriously: Why Maximizers Often Get Mired in Choices - Luan, Mo; Liu, Zhengtai; Li, Hong (Frontiers in Psychology, 2022)
Maximizing is a topic that has received significant attention from researchers and corporate organizations alike. Although extensive previous research has explored how maximizers behave in a decision scenario, a fundamental question remains about why they prefer a larger assortment regardless of whether the decisions are important or not. The current research attempts to explore the underlying mechanism of this phenomenon. Four surveys were conducted, and participants from Mturk or Credamo online platform were recruited (N = 922). The maximizing tendency was measured by either Maximization Scale or Maximizing Tendency Scale, and perceived importance as well as preference for large assortment were measured in different decision scenarios. Across four studies, we find that maximizers perceive the same decision as more important than satisficers (Study 1), and perceived importance serves as the mechanism underlying the maximizers’ preference for a large assortment (Study 2). In other words, in maximizers’ perceptions and interpretations, even seemingly trivial decisions are important enough to spend great efforts on a large assortment. We additionally identify a boundary condition of the effect – cost salience (Studies 3a and 3b). These findings illustrate a pioneering empirical exploration of the difference in the way maximizers and satisficers perceive their decision importance, and a reason for maximizers’ preference for a large assortment.